A self-doped conducting polymer "polyanthranilic acid": An efficient corrosion inhibitor for mild steel in acidic solution - Shukla S.K.; Quraishi M.A.; Prakash R. (My University, 2025)
In recent years, polyanilines have been reported as one of the efficient corrosion inhibitors for iron in acidic media. In view of the major limitation of insolubility of polyaniline, we propose the use of functionalized self-doped conducting polymer to get higher solubility and corrosion efficiency. The chemical synthesis of water soluble self-doped polyanthranilic acid using various oxidizing agents and for time intervals of polymerization is reported for the first time for the corrosion inhibition studies. The corrosion inhibition property of the polymer is demonstrated for mild steel in acidic environment using electrochemical impedance spectroscopy, Tafel polarization and weight loss methods. © 2008 Elsevier Ltd. All rights reserved.